2011
DOI: 10.1007/s10681-011-0411-4
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of race 1.2 Fusarium wilt resistance in four melon cultivars

Abstract: The resistance to Fusarium oxysporum f.sp. melonis (Fom) race 1.2 has been studied in melons, such as the Portuguese accession 'BG-5384' and in the Japanese 'Shiro Uri Okayama', 'Kogane Nashi Makuwa', and 'C-211', since a good characterization of the resistance is necessary before its introgression into commercial varieties. These four melon accessions showed a high level of resistance to races 0, 1, and 2 of Fom, indicating that the partial resistance to the race 1.2 previously detected may not have been race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…In both cases, further characterization of the resistance and selection are needed before the resistance can be incorporated into melon breeding programs. Indeed, up to now, resistance to race 1.2 is reported to be complex, controlled by multiple recessive genes with epistatic effects, which make its management difficult [13]. Besides, Herman and Perl-Treves [16] reported that resistance to this race is controlled by two recessive genes in the breeding line BIZ, and unfortunately, the molecular markers linked to those genes were not validated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In both cases, further characterization of the resistance and selection are needed before the resistance can be incorporated into melon breeding programs. Indeed, up to now, resistance to race 1.2 is reported to be complex, controlled by multiple recessive genes with epistatic effects, which make its management difficult [13]. Besides, Herman and Perl-Treves [16] reported that resistance to this race is controlled by two recessive genes in the breeding line BIZ, and unfortunately, the molecular markers linked to those genes were not validated.…”
Section: Discussionmentioning
confidence: 99%
“…For Fom race 1.2 inoculation experiments, disease severity in each inoculated plant was evaluated at 7, 15, 21, and 30 dpi (days post-inoculation) according to the same visual scale from 0 to 4, and the area under the disease progress curve (AUDPC) was estimated from those scores [13,15]. The AUDPC integrates both the intensity of symptoms and the time taken between inoculation and expression of symptoms.…”
Section: Analyses Of Molecular Markers For Fom Races 0 1 Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Segregation of the resistance response in these populations supported a model in which two complementary, recessive genes, designated fom-1,2a and fom-1,2b, are required to obtain full resistance. Recently, Chikh-Rouhou et al (2011) determined the mode of inheritance of resistance to Fom race 1,2 in lines BG-5384, Shiro Uri Okayama, Kogane Nashi Makuwa and C-211. The F 1 , F 2 , and reciprocal backcross generations from the crosses between the above four resistant accessions and 'Piel de Sapo', a Fom race 1,2 susceptible melon, were analyzed by inoculation with isolates belonging to the 1,2y and 1,2w pathotypes.…”
Section: Resistance To Fom Race 12mentioning
confidence: 99%